Utilization of Neuroimaging in Criminal Justice: Unveiling Truth Through Brain Technology - Cholidin, Achmad; Fernando, Zico Junius; Feka, Mikhael (Universitas Negeri Semarang (UNNES), 2024)
The integration of neuroimaging technology in criminal justice worldwide has opened new avenues for understanding the neural underpinnings of criminal behavior and improving the accuracy of legal processes. This paper explores the application of neuroimaging techniques, such as functional Magnetic Resonance Imaging (fMRI) and Positron Emission Tomography (PET), in the context of criminal investigations and trials. Neuroimaging provides insight into brain function related to intent, deception, memory, and cognitive control, which is critical in determining culpability and assessing mental states. By reviewing case studies and current research, this study evaluates the potential benefits and ethical challenges of using neuroimaging as evidence in court. The findings suggest that although neuroimaging holds the promise of improving the objectivity and reliability of criminal justice, its use should be conducted with caution due to legal, ethical, and technical limitations. The paper concludes with recommendations for the responsible integration of neuroimaging into legal practice to ensure fairness and protect the rights of individuals. The implications of these findings for criminal law enforcement in Indonesia are also discussed, highlighting the potential of applying neuroimaging techniques to improve the fairness and effectiveness of the legal system.